2019
DOI: 10.3390/antiox8090410
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl Trisulfide Protects Rat Brain Tissue against the Damage Induced by Ischemia-Reperfusion through the Nrf2 Pathway

Abstract: Stroke is a public health problem due to its high mortality and disability rates; despite these, the pharmacological treatments are limited. Oxidative stress plays an important role in cerebral damage in stroke and the activation of the nuclear factor erythroid 2-related factor 2 (Nrf2) confers protection against oxidative stress. Different compounds, such as diallyl trisulfide (DATS), have the ability to activate Nrf2. DATS protects against the damage induced in oxygen-glucose deprivation in neuronal cells; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…To investigate the molecular mechanism by which muscle antioxidant capacity was regulated by betaine, the mRNA expressions of antioxidant genes were measured in the present study. The Nrf2 is an important transcription factor that plays a fundamental role in cellular defense against reactive free radicals and other oxidant species ( Silva-Islas et al., 2019 ). HO-1 , a downstream antioxidant gene of Nrf2 signaling pathway, is involved in the oxidative degradation of heme ( Loboda et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the molecular mechanism by which muscle antioxidant capacity was regulated by betaine, the mRNA expressions of antioxidant genes were measured in the present study. The Nrf2 is an important transcription factor that plays a fundamental role in cellular defense against reactive free radicals and other oxidant species ( Silva-Islas et al., 2019 ). HO-1 , a downstream antioxidant gene of Nrf2 signaling pathway, is involved in the oxidative degradation of heme ( Loboda et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diallyl trisulfide (DATS), one of the major and biologically active components of garlic oil, exhibits a beneficial effect on the recovery of I/R injury. For example, it is suggested that DATS could be used for the treatment of I/R injury in brain tissues for its inhibitory effects on oxidative stress through Nrf2 activation ( Silva-Islas et al, 2019 ). Besides, DATS is also believed to own the ability for the promotion of angiogenesis ( Hayashida et al, 2017 ), which can be utilized for the protection of ischemic tissue in diabetic mice ( Yang et al, 2018 ) as well as the salvation of the ischemic limb ( Hsieh et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In rats receiving DATS decreased MDA levels were reported. Interestingly, Nrf2 induction increased in the cortex as well as SOD1 in the nucleus, SOD2 and glutathione S-transferase (GST) at both striatum and cortex levels [56]. SAC was able to exert cytoprotective effects, inducing Nrf2 and its downstream targets and suppressing JNK and p38 phosphorylation in cortical neurons exposed to OGD.…”
Section: Spice Bioactive Compoundsmentioning
confidence: 99%
“…In rats receiving DATS decreased MDA levels were reported. Interestingly, Nrf2 induction increased in the cortex as well as SOD1 in the nucleus, SOD2 and glutathione S-transferase (GST) at both striatum and cortex levels [ 56 ].…”
Section: Natural Compounds As Modulator Of Nrf2 Pathway In Stroke mentioning
confidence: 99%
See 1 more Smart Citation